Problems of Management of Social Processes in the Almaty Region of Kazakhstan - MYRZABEKOVA, Gaziza (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
The present article substantiates the role of forecasting as a method in the system of management, in the development and integration of social processes in the region and its territorial structures. It also analyzes the peculiarities arising from the nature and properties of regional systems and strengthening the regulatory functions of the state through the mechanism of distribution of state expenditures, and sets out the essence of a fundamentally new model of social protection in Kazakhstan and the classification of social standards, which is a practical framework of the managed forecasting.